SOCIAL INTEGRATION IN DAILY LIFE: A PROXY FOR PHYSICAL ACTIVITY. (11th November 2018) - Fingerman, K; Huo, M
Abstract: For nearly 3 decades, researchers have shown that people who are more socially integrated live longer and in better health. A variety of psychological and relationship mechanisms account for this association including relationship qualities and health. Yet, researchers have not considered associations between social ties and daily physical activity; social integration requires people to get up out of their chair. This study included men and women over age 65 (n = 313) who reported on their social networks, responded to Ecological Momentary Assessments (EMA) every 3 hours and wore Acticals to measure physical activity for 5 to 6 days. Findings revealed that throughout the day, engagement with a greater variety of social partners predicted higher physical activity in a 3 hour period. Further, engagement with non-family seemed to account for these findings. We discuss findings with regard to sedentary behaviors, social integration theory and weak ties.